Analysis of the Effect of DJ Transition Techniques on Discotheque Visitor Behavior: A Case Study of Entrainment at Panic Paradise Club - Rizal, Samsul; Suhendi Afryanto; Hinhin Agung Daryana (Postgraduate Program of Institut Seni Budaya Indonesia Bandung, 2024)
The phenomenon of trance that occurs when watching music performances, especially traditional music in Indonesia, is common and is often associated with the supernatural, beliefs, and other mystical aspects. However, scientific research has provided an explanation for this phenomenon. Entrainment, a condition in which the body of a living being is synchronized with the music’s emitting source (oscillator), is the scientific explanation for the phenomenon. This research focuses on how music in nightspots (discos) can make listeners reach the entrainment phase. The entrainment phase can be achieved if the beat of the music is stable when perceived by the listener. The researcher hypothesized that music transition techniques are very influential to achieve the entrainment phase. In addition, the individual and collective behavior of participants can influence other discotheque visitors. This research uses a qualitative method with a grounded theory approach. Data were collected through field observations with a number of participants in two trials. The first test (pre-test) was conducted with music from a disc jockey who was less proficient in transition techniques, while the second test (post-test) was conducted under the opposite conditions. The results showed that the participants were able to achieve the third phase of entrainment and affect other visitors collectively, which was not the case in the pre-test. This shows that entrainment can be achieved with effective music transition techniques from a disc jockey, and an individual’s entrainment state can influence other discotheque patrons both individually and collectively. The successfully achieved entrainment phenomenon is also able to explain the phenomenon of trance influenced by music.